Mouse-induced pluripotent stem cells differentiate into odontoblast-like cells with induction of altered adhesive and migratory phenotype of integrin. - Nobuaki Ozeki; Makio Mogi; Rie Kawai; Hideyuki Yamaguchi; Taiki Hiyama; Kazuhiko Nakata; Hiroshi Nakamura (PLoS ONE, 2013)
Methods for differentiating induced pluripotent stem (iPS) cells into odontoblasts generally require epithelial-mesenchymal interactions. Here, we sought to characterize the cells produced by a 'hanging drop' technique for differentiating mouse iPS cells into odontoblast-like cells that requires no such interaction. Cells were cultured by the hanging drop method on a collagen type-I (Col-I) scaffold (CS) combined with bone morphogenetic protein (BMP)-4 (CS/BMP-4) without an epithelial-mesenchymal interaction. We evaluated the expression of odontoblast-related mRNA and protein, and the proliferation rate of these cells using reverse-transcription polymerase chain reaction, immunofluorescence staining, and BrdU cell proliferation enzyme-linked immunosorbent assay, respectively. The differentiated cells strongly expressed the mRNA for dentin sialophosphoprotein (DSPP) and dentin matrix protein-1 (Dmp-1), which are markers of mature odontoblasts. Osteopontin and osteocalcin were not expressed in the differentiated cells, demonstrating that the differentiated iPS cells bore little resemblance to osteoblasts. Instead, they acquired odontoblast-specific properties, including the adoption of an odontoblastic phenotype, typified by high alkaline phosphatase (ALP) activity and calcification capacity. The cell-surface expression of proteins such as integrins α2, α6, αV and αVβ3 was rapidly up-regulated. Interestingly, antibodies and siRNAs against integrin α2 suppressed the expression of DSPP and Dmp-1, reduced the activity of ALP and blocked calcification, suggesting that integrin α2 in iPS cells mediates their differentiation into odontoblast-like cells. The adhesion of these cells to fibronectin and Col-I, and their migration on these substrata, was significantly increased following differentiation into odontoblast-like cells. Thus, we have demonstrated that integrin α2 is involved in the differentiation of mouse iPS cells into odontoblast-like cells using the hanging drop culture method, and that these cells have the appropriate physiological and functional characteristics to act as odontoblasts in tissue engineering and regenerative therapies for the treatment of dentin and/or dental pulp damage.